Buku Prestasi Santri berbasis Digital menggunakan Prinsip Postel - Muhammad Fahmi Faisal Hikmawan; Irfansyah Irfansyah (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
Recording students' learning activities at Quran Education Institute is still done manually, but reporting to the government (Kemenag) has gone through an online system. Teachers sometimes have to input data from the printed version into the digital system, increasing their burden. This research aims to create a Graphical User Interface (GUI) digital achievement book that will make it simpler for teachers to track the development and activities of their students' learning. In this study, the User-Centered Design (UCD) process was used, which included understand the context of use, specify user requirements, produce design solutions, and evaluate against requirements. Data was gathered by questionnaires and interviews and then analyzed using descriptive techniques. Postel principles apply in this Graphical User Interface (GUI) design to simplify input variations into interface elements. The study produces a GUI design of digital achievement books (SimpelQu) to make it easier for teachers to input information on Iqra learning (volumes, pages, reading descriptions and reading status). The System Usability Scale (SUS) technique was used to evaluate this design on five teachers to assess GUI usability. The SUS test yielded an average final score of 75, indicating its design has acceptable usability and is appropriate for assisting teachers.